Implementation of Marine and Fisheries Business Actor Card Policy (KUSUKA) in West Aceh Region - M. Akbar Ichtiar; Nodi Marefanda; Nellis Mardhiah (Universitas Teuku Umar, 2021)
This study discusses about implementation of the KUSUKA card policy in West Aceh Regency. KUSUKA Card is one of the mainstay service programs of the Ministry of Maritime Affairs and Fisheries to provide effective, efficient and targeted services to all members of the community who work in the marine and fisheries sector. This research uses qualitative method with a descriptive approach. The theory used in this research is the theory of the successful implementation of policy by Edward III. The result showed that the implementation of the KUSUKA card policy in West Aceh Regency was still not good because each indicator: Resources, Communication, Bureaucratic Structure and Disposition had not been fulfilled had not been fulfilled.